Speaker meaning, utterance meaning and radical interpretation in Davidson's 'A nice derangement of epitaphs'. Issue 2 (1st November 2017) - Smith, Imogen
It is central to Davidson's argument in 'A nice derangement of epitaphs' that a speaker's utterance can have a non-standard meaning, rather than that the speaker can mean something non-standardly when so uttering. Linguistic conventionalism typically holds that Mrs Malaprop, in uttering 'a nice derangement of epitaphs', might mean a nice arrangement of epithets but that her words do not. I suggest that Davidson's view of language provides him with good grounds to claim that the nonstandard meanings can be attributed to a speaker's utterances and not merely the speakers themselves. However, I also suggest that in many cases of interpretation of non-standard utterances, communication is successful because an interpreter first grasps the speaker's relevant intentions, rather than the meaning of the utterance itself. Indeed, in a single communicative exchange containing an innovative utterance successfully interpreted, it is not the meaning of the utterance that one is entitled to say is identified, but what a speaker means to communicate when he produces an utterance.